NETWORKED DEMOCRACY: THE ROLE OF ALGORITHMS IN FREEDOM OF EXPRESSION AND POLITICAL PLURALISM - Martins , Kennedy da Nobrega; Rodrigues, Alexandre Manuel Lopes (Seven Editora, 2024)
In recent decades, social media algorithms have redefined the digital environment, profoundly influencing freedom of expression and political pluralism. In light of this, this research investigates how these algorithms, by segmenting content according to user behavior, promote the creation of "echo chambers" and "digital bubbles" that reinforce polarization and limit access to divergent perspectives. The methodology adopted was the bibliographic and documentary review, with analysis of academic and legal sources on the impact of algorithms and computational propaganda on the formation of public opinion. The results indicate that, by prioritizing engagement over informational diversity, algorithms favor polarized environments, hindering democratic dialogue and encouraging the dissemination of extremist content. It is concluded that public policies and regulations that promote the transparency of algorithms and encourage informational diversity are essential to preserve the integrity of the digital public sphere. DOI:https://doi.org/10.56238/sevened2024.037-079